The Use of ANOVA in Comparative Analysis of Exchange Rates in Indonesia - Renaldo, Nicholas; Vomizon, Rodle; Nuonnad, Diaz Othman; Okšav, Nitram; Hilas, Rajah Abdulqadir (Nexus Synergy: A Business Perspective, 2023)
The aim of research regarding the use of Analysis of Variance (ANOVA) in comparative analysis of exchange rates in Indonesia is to analyze differences in foreign currency exchange rates. This research uses ANOVA analysis to determine differences in exchange rates in Indonesia. The research results show that the calculated F value is less than the F table, showing that the difference between the groups is not statistically significant. In the context of foreign currency at BCA, BI, BNI, and KMK, based on the analysis results, there is no significant difference between the foreign currency exchange rates at these banks. It is hoped that future research can use other methods to measure exchange rate differences more precisely, such as Two Way ANOVA or other statistical methods.